PENGARUH SUBSTITUSI TEPUNG IKAN DENGAN TEPUNG MAGGOT DALAM PAKAN TERHADAP PERFORMA AYAM MERAWANG - Prasetyo, Vian Eko; Kardaya, Dede; Wahyuni, Dewi (Universitas Djuanda, 2024)
Fish meal is a protein source feed ingredient in poultry rations but the availability of fish meal is still limited. Maggot Black Soldier Fly (BSF) can be utilized as an alternative feed to replace fish meal because it has a protein content from 40-50%. The research was conducted at Papidoka Farm (Caringin-Bogor) from October-November 2023. This study used 60 merawang chickens on 9 weeks old with body weight of 721.8±68.6 g. The study used a Completely Randomized Design (CRD) with 5 treatments and 4 replicates for each treatment. The test results were analyzed using SPSS 2023 for analyses of variance (ANOVA) and Duncan's test. The treatments were as follows: P0 = 0% maggot meal + 10% fish meal, P1 = 2.5% maggot meal +7.5% fish meal, P2 = 5% maggot meal + 5% fish meal, P3 = 7.5% maggot meal + 2.5% fish meal, P4 = 10% maggot meal + 0% fish meal. The observed variables were body weight, body weight gain, feed consumption, feed conversion, mortality, Feed cost per gain (FC/G), and income over feed cost (IOFC). The results of the analysis of variance showed that the substitution of fish meal with maggot meal in merawang chickens had no significant effect (P>0.05) in body weight, body weight gain, feed consumption, and feed conversion. It was concluded that the substitution of fish meal with maggot meal at the level of 2.5% - 10% could not increased the performance of merawang chickens in body weight, body weight gain, feed consumption, and feed conversion.